2018
DOI: 10.1175/jpo-d-17-0195.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Swell on the Atmospheric Boundary Layer under Nonneutral Conditions

Abstract: The anomalous phenomena induced by the prevailing swell at low wind speeds prevent a complete understanding of air–sea interaction processes. Many studies have considered this complex problem, but most have focused on near-neutral conditions. In this study, the influence of the swell on the atmospheric boundary under nonneutral conditions was addressed by extending the turbulent closure models of Makin and Kudryavtsev and the Monin–Obukhov similarity theory (MOST; Monin and Yaglom) to the existence of swell an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Under swell conditions, however, field measurements (Högström et al, ; Högström et al, ; Smedman et al, ) show that swell waves can exert a singular point in the wind profile, which cannot be modeled within the framework of the traditional MOST. The invalid MOST was further confirmed by direct numerical simulation (Kihara et al, ; Sullivan et al, ), large‐eddy simulation (Jiang et al, ; Nilsson et al, ; Sullivan et al, and Sullivan et al, ), and simplified theoretical models (Hanley & Belcher, ; Semedo et al, ; Song et al, and Zou et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…Under swell conditions, however, field measurements (Högström et al, ; Högström et al, ; Smedman et al, ) show that swell waves can exert a singular point in the wind profile, which cannot be modeled within the framework of the traditional MOST. The invalid MOST was further confirmed by direct numerical simulation (Kihara et al, ; Sullivan et al, ), large‐eddy simulation (Jiang et al, ; Nilsson et al, ; Sullivan et al, and Sullivan et al, ), and simplified theoretical models (Hanley & Belcher, ; Semedo et al, ; Song et al, and Zou et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…The wave‐induced stress can be calculated through the wave spectrum, which has been widely used to correct the turbulent stress to be consistent with the actual total stress (Babanin et al, 2018; Chen et al, 2019; Zou et al, 2018). Here, we apply the same method into our observations and find that this correction is feasible (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…However, the actual height of the critical layer with the swell impact is difficult to be determined. Previous MABL models were generally developed based on the assumption of constant flux layer to simulate vertical wind profiles and wave-driven wind speed under swell conditions (Semedo et al, 2009;Zou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the land surface, the ocean surface is mobile; therefore, surface waves, have a crucial impact on the stress vector (Chen et al, 2019;Pan et al, 2005;Zou et al, 2018Zou et al, , 2019. Giovanangeli et al (1994) showed that the deviation of wind stress from the wind direction depends on the swell direction and steepness based on the wind-wave tunnel measurements.…”
Section: Introductionmentioning
confidence: 99%